2015
DOI: 10.1002/ccd.25952
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term outcomes in diabetes patients undergoing percutaneous coronary intervention with bivalirudin compared with heparin and glycoprotein IIb/IIIA inhibitors: A meta‐analysis of randomized trials

Abstract: Background: Diabetes patients undergoing percutaneous coronary intervention (PCI) have more complications than nondiabetes patients, including increased long-term mortality. Use of bivalirudin versus heparin and glycoprotein IIb/IIIa inhibitors (GPI) in diabetes patients undergoing PCI and its effect on long-term mortality were evaluated in few randomized trials, but with conflicting results. Methods: We searched the literature for randomized controlled trials that compared heparin and GPI therapy with bivalir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…These results were comparable with a number of meta-analyses conducted recently (Cavender and Sabatine, 2014; Cassese et al, 2015; Nairooz et al, 2015). However, in another meta-analysis conducted by Navarese et al (2015), no significant difference was found in the risk for major bleeding (based on the primary study definition) between bivalirudin-based regimens and heparin-based regimens with provisional GPI use (Navarese et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results were comparable with a number of meta-analyses conducted recently (Cavender and Sabatine, 2014; Cassese et al, 2015; Nairooz et al, 2015). However, in another meta-analysis conducted by Navarese et al (2015), no significant difference was found in the risk for major bleeding (based on the primary study definition) between bivalirudin-based regimens and heparin-based regimens with provisional GPI use (Navarese et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…A meta-analysis conducted by Nairooz et al (2015) suggested that the lower risk of major bleeding offered by bivalirudin-based regimens may be driven by mandating the use of a GPI (Nairooz et al, 2015). The improved safety of bivalirudin-based regimens could be largely attributed to the more frequent co-administration of GPIs with heparin.…”
Section: Discussionmentioning
confidence: 99%
“…There was a meta-analysis published in 2015 by Nairooz et al, [18] in which they reported that the application of Biva significantly lower levels of major bleeding and mortality compared with that resulting from heparin and GPI use in diabetes patients undergoing PCI. However, our findings are not consistent with these results.…”
Section: Discussionmentioning
confidence: 99%
“…The diabetic prothrombotic state differentially increases ischemic more than bleeding risk particularly in individuals requiring insulin treatment . Nairooz et al's and other meta‐analyses, as most precise available estimates, demonstrate that bivalirudin with provisional IIb/IIIa use is superior to routine IIb/IIIa therapy due to less bleeding and lower one‐year mortality in diabetics . Except for the mortality benefit of bivalirudin, this subgroup result is consistent with the outcome in all PCI patients: less bleeding and equivalent ischemic outcomes between bivalirudin and routine IIb/IIIa use.…”
mentioning
confidence: 52%